Analysis and Design of Solar Power Plants as Energy Source for Green Hydrogen Production at PLTU Banten 2 Labuan - Permana, Indra Setia; Devianto, Hary; Gusnawan, Pri Januar; Nainggolan, Irwan Firmanto (Universitas Ibn Khaldun Bogor, 2026)
Climate change is a global challenge that demands collective efforts, including from Indonesia, which aims to reduce greenhouse gas emissions by 31.89% through domestic efforts and 43.20% with international support. As part of a state-owned company, PLN contributes to this effort by integrating hydrogen business development into its strategic program. PLTU Banten 2 Labuan has a hydrogen plant with the potential to produce excess hydrogen for economic use. This research simulates three hydrogen production schemes to optimize performance and cost efficiency. The analysis reveals significant differences in terms of CAPEX, OPEX, LCOH, NPV, PI, IRR, DPP, and carbon emissions. Scheme 4, despite having the lowest emissions and OPEX, has very high CAPEX, with the highest LCOH of 7.41 USD/kg and poor financial performance (negative NPV of -217,908.33 USD, IRR of 3.62%, and PI of 0.59). Scheme 2, with the lowest LCOH of 3.79 USD/kg, is attractive but results in high carbon emissions (318,864 kg CO₂e). Scheme 5, with moderate CAPEX and LCOH of 4.03 USD/kg, performs best overall, showing positive financial indicators NPV of 163,593.97 USD, PI of 3.14, IRR of 32.62%, and a short DPP of 3.2 years. Scheme 5 is the most optimal and recommended for further implementation.